Association between psychosocial stressors and temporomandibular disorders in clinical dental students: a cross-sectional study - Abdullah Alqarni; Jagadish Hosmani; Saeed Alassiri; Ali Mosfer A. Alqahtani; Ali Alfaifi; Shuayl Abdulaziz Al Jazea (PeerJ, 2025)
Background Temporomandibular disorders (TMDs) comprise an extensive spectrum of conditions that originate from diverse complex components of the temporomandibular joint. It is generally acknowledged that the biopsychosocial model is the preeminent framework for understanding the aetiology of TMDs. Anxiety, depression, and tension are among the psychological disorders that are commonly observed in dental students. The current research probed the propinquity of psychosocial stressors and TMD-like symptoms among clinical dental undergraduates residing in the Aseer region of Saudi Arabia, with a specific emphasis on the functional implications for their overall well-being. Methods This research included 89 clinical dentistry students who completed online questionnaires. The Patient-Reported Outcomes Measurement Information System (PROMIS) and Oral Health Impact Profile for Temporomandibular Disorders (OHIP-TMD) were used in these surveys. The trait-related attributes of TMD impacting the oral health profile were assessed using principal component analysis. Demographic factors for anxiety and TMD were examined using linear regression. The psychosocial and functional variables of the OHIP-TMD were compared with those of anxiety in the general regression system. Results The mean Oral Health Impact Profile (OHIP) value was 0.60, with a standard deviation of 0.61, indicating that the majority of respondents reported no or infrequent impacts on their oral health profile. Gender was a significant predictor of OHIP scores (P < 0.05), with females reporting higher scores. Despite these higher scores among females, the overall impact on oral health remained minimal for most respondents. The average PROMIS score was 11.12, with a standard deviation of 3.84. The PROMIS regression analysis on demographic variables yielded an R2 value of 0.092, F(4,78) = 5.691, with significance at P < 0.05. Gender emerged as the most significant predictor of PROMIS scores (P < 0.05), with females reporting higher scores. Once again, despite the higher scores among females, the overall impact remained low for most respondents. An analysis using a general linear model revealed a significant correlation between heightened anxiety levels and an increase in both psychosocial problems and physical function. Conclusion Although the majority of respondents reported minimal impacts on their oral health, anxiety remained a significant issue among female clinical dentistry students at the College of Dentistry in Aseer Province, Kingdom of Saudi Arabia. This anxiety was closely linked with psychological distress and impaired oral physical function. Beyond the realm of dental health, anxiety also had a profound effect on academic performance and student engagement. Therefore, addressing student anxiety is essential for enhancing overall well-being and academic success.